Advancing career counselling research and practice using a novel quantitative+qualitative approach to elicit clients’ advice from within - Maree, J.G. (South African Journal of Higher Education, 2020)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">This article reports on the results of providing career counselling to a purposefully selected first-year university student experiencing career indecision. An integrated approach based on qualitative and quantitative techniques was used to engage the student (the research participant) in conversations, reflections and meta-reflections on how to find meaning and purpose in his current studies and also in his future career-life. An intrinsic, single-case study involving a purposefully selected participant and the use of two newly developed instruments was undertaken to demonstrate the practical implementation of the new approach. The intervention helped the participant identify his career-life themes and later choose a field of study that would enable him to fit work into his life, design and live a successful life and make meaningful social contributions. Future research should investigate the longitudinal value of the approach and its use in group contexts.